- 1-214-256-5804
- info@tutorpace.com

The given expression: 2x+ 4x-18 = 0

The above given algebraic expression is a trinomial since it contains three terms.

In order to solve for the unknown variable ‘x’, here we can first simplify the expression.

This means that we can combine the like terms together.

Hence we get, 2x+ 4x–18 = 0->6x- 18= 0.

Now we can solve for ‘x’-> 6x = 18-> x= 18/6 = 3.

Therefore the value of ‘x’ is 3.

The given expression: 6p – 9p – 24= 0

The above given algebraic expression is a trinomial since it contains three terms.

In order to solve for the unknown variable ‘p’, here we can first simplify the expression.

This means that we can combine the like terms together.

Hence we get, 6p – 9p – 24= 0

Now we can solve for ‘p’==> -3p = 24==> p= 24/-3 = -8.

Therefore the value of ‘p’ is -8.